Norwegian Antarctic whaling seen through the eye of the camera - Barr, Susan (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; fotografi; historie; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk

A century of German interests in modern whaling, 1860s-1960s - Barthelmess, Klaus (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Nordmenn; Sørishavet; Tyskland; hvalfangere; pelagisk hvalfangst; økonomi

Survival against all odds? Shore station whaling at South Georgia in the Pelagic. Era, 1925-1960 - Basberg, Bjørn L (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk; økonomi; økonomisk historie

Den farlige isen i Antarktis - Ekra, Siv Ingrid Skau (Norges teknisk-naturvitenskapelige universitet SINTEF, 1993)
All is i antarktiske havområder er flerårig under den antarktiske sommeren. Slik is er særlig sterk og hard og smelter ikke. I store bølger får de farlige stykkene stor fart. Treffer de en båt, skjer det med stor kraft.
Keywords: Sørishavet; båter; isforholdene; populærvitenskap

Hvalfangstlæge for 40 år siden - Husby, Jakob; Kolltveit, Bård (Norsk sjøfartsmuseum. Årsberetning, 1993)
Keywords: Anglo Norse ekspedisjonene; Sørishavet; erindringer; historie; hvalfangst; hvalkokerier; pelagisk

Kapittel 3 - Arbeidsløsheten. Kapittel 6 - Den lokale organisasjonen i 30-åra - Magdahl, Jørn (Framnæsarbeidernes historie, 1993)
Keywords: Sørishavet; Vestfold; arbeiderbevegelse; byhistorie; hvalfangere; hvalfangstindustri; hvalindustri; næringsliv

Ice algae during EPOS, leg 1: assemblages, biomass, origin and nutrients - Syvertsen, Erik E; Kristiansen, Svein (Polar Biology, 1993)
Keywords: Sørishavet; Weddellhavet; alger; biomasse

Vel blåst! : kommandør Chr. Christensens hvalfangstmuseum 75 år : 1917-1992 - Wexelsen, Einar (Kommandør Chr. Christensens hvalfangstmuseum, 1993)
Keywords: Christen Christensen; Norge; Sørishavet; historie; hvalfangst; hvalindustri; museer

Working Conditions and Work-related Injuries and Illnesses on board Norwegian Floating Factories after World War II - Wexelsen, Einar (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Sørishavet; arbeidsforhold; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; medisin